2023
DOI: 10.1128/spectrum.02972-22
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Carbapenem and Colistin Resistant Gram-Negative Bacteria Colonizing Immunocompromised SARS-CoV-2 Patients Admitted to Some Libyan Hospitals

Abstract: In this work, we describe, for the first time, the occurrence of carbapenem-resistant bacteria colonizing COVID-19 patients who developed hospital-associated infections with carbapenemase-producing, Gram-negative bacteria at some isolation centers of COVID-19 in the eastern part of Libya. Our results confirmed that the overuse of antimicrobials, such as carbapenem antibiotics, during the COVID-19 pandemic has led to the emergence of multidrug-resistant bacteria, mainly K. pneumoniae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…K. pneumoniae is considered one of the major causes of global AMR burden, being among the top five most widespread nosocomial pathogens [ 24 ], and the World Health Organization (WHO) identified ESC- and carbapenem-resistant K. pneumoniae as a critical public health threat [ 25 ]. This study confirms that carbapenem-resistant K. pneumoniae are a major health issue in the Tripoli University Hospital, and most probably throughout the whole country according to the few publications on AMR in Libya [ 12 ]. Here, of the 54 isolates collected for their MDR phenotype, 49 belonged to the K. pneumoniae species, of which 35 presented at least one carbapenemase gene.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…K. pneumoniae is considered one of the major causes of global AMR burden, being among the top five most widespread nosocomial pathogens [ 24 ], and the World Health Organization (WHO) identified ESC- and carbapenem-resistant K. pneumoniae as a critical public health threat [ 25 ]. This study confirms that carbapenem-resistant K. pneumoniae are a major health issue in the Tripoli University Hospital, and most probably throughout the whole country according to the few publications on AMR in Libya [ 12 ]. Here, of the 54 isolates collected for their MDR phenotype, 49 belonged to the K. pneumoniae species, of which 35 presented at least one carbapenemase gene.…”
Section: Discussionsupporting
confidence: 84%
“…The occurrence of ESC- and carbapenem-resistant Enterobacterales, among which K. pneumoniae and, to a lesser extent, E. coli , have been evidenced by our study in Tripoli, and by Slimene et al in Sirte, Benghazi and Shahat [ 11 , 12 ], strongly suggests that these pathogens have widely disseminated in hospitals throughout Libya. Our results showed that resistance to last-resort antibiotics (ESC, carbapenems, amikacin, colistin) is conferred by a large variety of genes, plasmids and clones, thus making their transmission more efficient.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Additionally, carbapenem-resistant Klebsiella pneumoniae carrying OXA-48 was detected [ 13 ]. Worryingly, carbapenem and colistin-resistant bacteria were also isolated from COVID-19 patients in Libya [ 14 ]. ESBL and MBL producing Gram-negative bacteria were isolated from operating theaters and ICU of Sabha Medical Center, Sabha city, Libya [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%